Boosting English Language Acquisition with Engaging Game-Based Activities (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
This article presents the findings of a research study investigating the effectiveness of utilizing games in English language learning. The study demonstrates a significant increase in vocabulary, grammatical proficiency, and communicative skills among English learners who engaged in game-based activities